Categorical Perception, Phonological Deficit, and Dyslexia: A Systematic Review - López-Zamora, Miguel; Porcar-Gozalbo , Nadia; López-Chicheri García, Isabel; Cano-Villagrasa , Alejandro (Revista de Investigación en Logopedia, 2026)
Categorical perception (CP) of speech is a phonological process essential for reading development, as it enables the classification of acoustic stimuli into discrete categories, and has been proposed as a potential explanatory factor for phonological difficulties in dyslexia. Nevertheless, significant discrepancies remain regarding its functional role, experimental assessment, and diagnostic utility. This study presents a systematic review of recent literature on CP in children with dyslexia. Eighteen empirical studies published between 2010 and 2024 were examined, analyzed in terms of design, measures, and findings. Studies were included if their samples allowed for the evaluation of the coexistence of difficulties in CP and phonological processing within a diagnosis of dyslexia. The main objectives were to assess performance in phoneme categorization tasks and to explore the relationship between CP and associated phonological deficits. Results were organized into three thematic axes: (1) the relationship between CP and phonological awareness; (2) difficulties in perceptual anchoring and in learning new auditory categories; and (3) atypical phonological processing characterized by allophonic perception. Overall, the studies revealed a significant, though not universal, association between CP and reading skills, as well as specific alterations in auditory adaptation mechanisms and phonological awareness. While the findings support the existence of CP deficits in dyslexia, methodological limitations and critical perspectives questioning its validity as a construct were also identified. The need to revise classical paradigms and to integrate more ecological and dimensional approaches to phonological processing is emphasized in order to broaden our understanding of the role of CP in reading.